Analisa Tingkat Keselamatan Lalu Lintas pada Simpang Empat Puncak Jelutung dengan Metode Traffic Conflict Technique (TCT) - M Darwin; Amsori M Das; Ari Setiawan (Jurnal Talenta Sipil, 2022)
Accidents can occur due to several factor such as road, environmental and human factors. Jelutung peak red light intersection is a place that is prone to accidents due to conflicts between vehicles and other vehicles or between vehicles and pedestrians. The four-peak Jelutung intersection has a fairly large input and output capacity, and a fairly high density alternately in each lane during peak hours. This study aim to analyze traffic conflicts and examine the problems or damage that occurred at the intersection of Jl. Hayam Wuruk – Jl. D.I Panjaitan – Jl. Dr. Sumbiyono – Jl. Gajah Mada using the Traffict Conflict Technique (TCT) method which caused an accident. The method used in collecting data in this research is a field survey at 07:00-09:00 WIB. The result obtained are 8 types of conflicts that occur at the highest peak hour at 07:45-08:45 WIB, with the highest traffic violations occurring in type 7 conflict, namely with 87 cases of violations which are potential Serious Conflicts, in the shortest Time To Accident (TA) 0.18 seconds and the longest time is 0.53 seconds. Conflicts that occur are caused by vehicle factors, damaged road conditions, lack of complementary road facilities such as road marking and traffic signs, and lack of awareness of road users in obeying traffic regulations.